Minding minds : evolving a reflexive mind by interpreting others - Bogdan, Radu J. (MIT Press, 2000)
Drawing on philosophical, psychological, and evolutionary perspectives, Bogdan analyzes how primates create the resources for ""metamentation""â__the ability of the mind to think about its own thoughts.
"A Bradford book."
Keywords: Philosophy of mind.; Self-knowledge, Theory of.; Other minds (Theory of knowledge); Metacognition.; Other (Philosophy); Philosophie de l'esprit.; Connaissance de soi.; Altérité.; Métacognition.; PHILOSOPHY -- Mind & Body.; Metacognition; Philosophy of mind; Self-knowledge, Theory of; Metacognitie.; Reflexiviteit.; Primaten.; Mensen.; Evolutie.